Correction: Modeling of core-shell magneto-electric nanoparticles for biomedical applications: Effect of composition, dimension, and magnetic field features on magnetoelectric response. - Serena Fiocchi; Emma Chiaramello; Alessandra Marrella; Giulia Suarato; Marta Bonato; Marta Parazzini; Paolo Ravazzani (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0274676.].